A comparative histologic study on furcal perforation repair with Root MTA and Pro Root MTA in fully developed teeth in dog - Rahimi S.; Jodeiri B (Tehran University of Medical Sciences, 2005)
Background and Aim: The goal of endodontics is to seal the root canal system from the orifice to apical constriction completely and tridimensionally.Hence perforations during root canal therapy, because of caries or resorptions must be sealed and obturated with ideal materials. The aim of this study was to histologically compare two kinds of mineral trioxide aggregate Root MTA and Pro Root MTA for furcal perforation repair in developed teeth in dog. Materials and Methods: In this experimental study, thirty teeth consisting of second, third and fourth mandibular premolars of five German shepherd dogs were selected. Twenty-four teeth were randomly divided into four experimental groups (6 teeth each). One pair of Root MTA and Pro Root MTA groups studied in one month and the other in three months intervals. Positive and negative control groups was each contained three teeth. In positive control group, perforations were not treated and negative control group contained intact teeth. In experimental groups perforations repaired after one week exposure to oral cavity with Root MTA or Pro Root MTA. After time intervals animals were subjected to vital perfusion and 6 m histologic sections were prepared. Inflammation and hard tissue formation were ranked by Cox criteria. Data were analysed using Mann-Whitney and Chi-Square statistical tests with P0.05). Conclusion: Mineral Trioxide Aggregate is an adequate material for furcal perforation repair in dog's teeth. Root MTA could be a good substitute for Pro Root MTA considering the lower cost and similar characteristics.